Potassium 2-iodobenzenesulfonate monohydrate - Arshad, Muhammad Nadeem (International Union of Crystallography, 2008)
In the crystal structure of the title compound, K(+)·C(6)H(4)IO(3)S(−)·H(2)O, the potasium cation is 2.693 (3)–2.933 (3) Å from the sulfonate and water O atoms (including symmetry-related atoms) and forms a two-dimensional sheet-like structure in the bc plane, with the iodobenzene rings protruding above and below. The water molecule of crystallization is hydrogen-bonded to sulfonate O atoms within this two-dimensional arrangement. Symmetry-related iodobenzene rings are arranged perpendicular to one another with the I atom ca 4.1 Å from the centroid of the neighbouring benzene ring. In the crystal structure, these two-dimensional sheet-like supramolecular structures are arranged parallel to one another, stacked along the a-axis direction, with the benzene rings interdigitated.